(untitled) (Revista Electrónica Diálogos Educativos. REDE, 2017)
This article is part of the development of the doctoral thesis entitled "Educational policy and practice. Meanings assigned actors from public high schools to the concept of educational policyâ€. Its aim is to look into the concept of educational policy inÂ Chile, from an underexplored perspective, distinct from traditional conceptions and positivism, and understood rather from a hermeneutic point f view. This is because educational policy has an interpretive character, which comprises a critical analysis of government actions, which in turn cause an effect on school communities and their participants. In this sense, the policy is understood from the textual and discursive viewpoints, to what is put into action. This refers to the process of translation and interpretation by the school actors regarding educational policies adopted by their respective governments, which give them their own senses and meanings. The raised perspective opens a field to think and analyze education policy in Chile beyond its regulatory and institutional frameworks, but rather from daily school and its discursive practices. Without denying, in turn, that the school is part of a complex system where multiple actors and varied relationships must also be considered.